Experimental study of drainage of surface water by drainage layers of airdrome pavement under conditions of non-stationary filtration - Баришпол, Л. І. (Proceedings of National Aviation University (archive), 1998)
Presented are the materials of airdrome pavement of the process of non-stationary filtration with the aim to obtain experimental dependence of drainage time on the capacity of the drainage layer and its hydraulic slope. The drainage layer was made of various filtering materials: crushed stone, gravel and medium-grained sand. The obtained result can be used for verification of authenticity of certain theoretical dependences